Is the Bucharest Convention on the protection of the Black Sea against pollution still a matter of general concern? Has it reached its purpose? - Ileana Anca Duşcă; Ana-Maria Moraru (IBSU Scientific Journal (IBSUSJ), 2011)
If one takes into account the challenges that the Black Sea faces eutrophication, chemical pollution, threats to biodiversity and dramatic reduction of living marine resources, mainly due to the inappropriate conservation measures regarding the fishing areas at the maritime basis - the question that arises is whether we can assert after 20 years of application - that the Bucharest Convention on the protection of the Black Sea against pollution is still useful, that it has reached its purpose. The question is favored by the fact that the European Union seems more and more concerned with cooperation in the area, which also results from the former Communication of the Commission Black Sea Synergy a New Regional Cooperation Initiative, COM(2007)160.
Keywords: Q53; Q58; 330; chemical pollution; threats to biodiversity